2005
DOI: 10.1016/j.jvs.2005.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous nitric oxide modulates the systemic inflammatory response and improves kidney function after risk-situation abdominal aortic surgery

Abstract: In our experimental model, prophylactic treatment with the NO donor molsidomine regulates the systemic inflammatory response and minimizes damage at the kidney level. Clinical Relevance The importance of this article resides in the fact that an experimental study that clarifies the effect of the donors of NO under circumstances as similar as possible to those of the human clinic, such as aortic surgery under hypovolemic shock (ruptured aortic aneurysm) have been little studied, most of these studies being perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
9
0
9
Order By: Relevance
“…First, NO acts as a potent vasodilator, preventing platelet aggregation and leukocyte adhesion at the microcirculatory level, 23,24 thereby contributing to maintaining the microcirculatory flow after ischemia reperfusion. Lozano et al 25 found that infusion of another NO donor, molsidomine, resulted in the decrease of renal damage and prevention of local inflammation including leukocytes infiltration after suprarenal aortic clamping in pigs as found in this study. In a different study, Hosgood et al 26 reported that reperfusion of ischemic kidney with the NO donor sodium nitroprusside resulted in an increase in RBF after warm ischemia in pigs.…”
Section: Discussionsupporting
confidence: 77%
“…First, NO acts as a potent vasodilator, preventing platelet aggregation and leukocyte adhesion at the microcirculatory level, 23,24 thereby contributing to maintaining the microcirculatory flow after ischemia reperfusion. Lozano et al 25 found that infusion of another NO donor, molsidomine, resulted in the decrease of renal damage and prevention of local inflammation including leukocytes infiltration after suprarenal aortic clamping in pigs as found in this study. In a different study, Hosgood et al 26 reported that reperfusion of ischemic kidney with the NO donor sodium nitroprusside resulted in an increase in RBF after warm ischemia in pigs.…”
Section: Discussionsupporting
confidence: 77%
“…Nitrite is unique in that it will be reduced to NO preferentially under hypoxic conditions and might thus provide NO where needed (Raat et al, 2009). This can less systematically be obtained with NO donors which were shown to induce beneficial (Lozano et al, 2005;Li et al, 2009), no (Hoshida et al, 1996;Zhu et al, 1996) or even detrimental (Mori et al, 1998) effects in I/R models.…”
Section: Introductionmentioning
confidence: 99%
“…Kuru et al (15) suggested that increase of renal injury occured with decrease of NO synthesis after chronic NOS inhibition. In another study (16), endogenous NO donor (molsidomine) was shown to improve kidney functions after abdominal aorta surgery. In our study, creatinine and urea levels were compared, and no significant difference was found between IR and IR+SNP groups.…”
Section: Discussionmentioning
confidence: 97%